Next directions in the neuroscience of cancers arising outside the CNS - Amit, Moran; Anastasaki, Corina; Dantzer, Robert; Demir, Ihsan Ekin; Deneen, Benjamin; Dixon, Karen O.; Egeblad, Mikala; Gibson, Erin M.; Hervey-Jumper, Shawn L.; Hondermarck, Hubert; Magnon, Claire; Monje, Michelle; et al. (Cancer discovery, 2024)
The field of cancer neuroscience has begun to define the contributions of nerves to cancer initiation and progression; here, we highlight the future directions of basic and translational cancer neuroscience for malignancies arising outside of the central nervous system.